Prediction of blood-brain barrier penetration of meta-/para-Alkoxyphenylcarbamic acid Esters bearing substituted N-Phenylpiperazine fragment (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The present study deals with blood-brain barrier (BBB) passive penetration of the substances labelled as 7a7d and chemically referred to as 1-[3-(Y-alkoxyphenylcarbamoyloxy)-2-hydroxypropyl]-4-(2-methylphenyl) piperazinium chlorides. Following their chemical structures, they could be classified as prospective ?-/?-adrenoceptor blockers. Such groups are known, among others, by their adverse reactions on central nervous system due to their transport across the BBB. The lipophilicity as the main parameter of the BBB permeability predictions is presented by the values of partition coefficient which was experimentally estimated using shake-flask method in two different partitions, i.e. in octan-1-ol/buffer and cyclohexane/buffer as well. The in silico models which were used are based on the correlation between the log BB and the ? log P readouts (the log P value estimated in octan-1-ol/buffer minus the one estimated in cyclohexane/buffer) whereby log BB is primary transfer marker for such compounds entering brain from blood. Besides the log BB outputs, some other molecular physicochemical descriptors have to be generated. According to the results obtained by using Young, Kaliszan, Kelder, Clarks, Pan, Abraham, Feher and van de Waterbeemd models, probably none of the currently investigated compounds will permeate across the BBB. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21854 Dhaka Univ. J. Pharm. Sci. 13(1): 7-14, 2014 (June)